Edukasi dan Sosialisasi Hak Kekayaan Intelektual (HKI) Bagi Pengrajin Batik Melindungi Motif dan Desain Tradisional - Idham Lakoni; Yola, Tasya; Bayu Saputra; Echi Susanti; Dina Karadita Putri; Iqbal Andrian (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The motifs and designs of traditional batik are an important part of Indonesia's cultural heritage, which holds high aesthetic and economic value. However, the low understanding of batik artisans about intellectual property rights (IPR) has led to many traditional works being vulnerable to imitation or claims by others without permission. This research aims to provide education and outreach regarding the importance of IPR protection to batik artisans, particularly in terms of copyright and industrial design. The methods used include counseling, interactive discussions, and the distribution of educational materials in batik craft centers. The results of the activities indicate an increase in participants' knowledge about relevant types of IPR, registration procedures, and the legal and economic benefits of IPR protection. This education is expected to encourage awareness and active participation of artisans in registering their works, so that traditional batik motifs and designs remain protected, preserved, and sustainable.